Trichosanthes dioica Roxb.: Pharmacognostic standardization of the female leaves with special emphasis on the microscopic technique - Saurabh Singh; M G Chauhan; Lalit Machawal (Wolters Kluwer Medknow Publications, 2011)
Objectives: Standardization is essentially a measure for ensuring the quality control of herbal drugs. But the gender of the plant affecting the quality of crude drugs does not appear to have been taken care of so far. Today, sophisticated modern research tools for the evaluation of the plant drugs are available but the microscopic method is one of the simplest and cheapest methods. Methods and Materials: The pharmacognostic investigation of the fresh, powdered, and anatomical sections of the female leaves of Trichosanthes dioica Roxb. was carried out to determine its bioprospective constants. Results and Discussion : Externally, the leaves possess a cordate base, a sinuate and dentate margin, an acute to acuminate apex, and both surfaces are very rough with rigid hair surface. Internally, it shows the presence of anomocytic stomata, unicellular, and both glandular and simple covering trichomes scattered as such throughout or attached with the cells of the epidermis. Majority of the glandular trichomes are with a four-to-five-celled uniseriate stalk and unicellular head; very few are short and with uni- to bicellular stalk and uni- to multicellular head especially from that of the petiole region. Simple covering, multicellular, uniseriate thick-walled trichomes are of various sizes. Usually cells of both simple and glandular trichomes are often embedded with cystolith. Phytochemical studies of the powdered leaves revealed the presence of alkaloids, resins, glycosides, flavonoids and some carbohydrates. The pharmacognostic profile of the leaves will assist in the standardization for quality, purity, and sample identification.